ARHGAP36 regulates proliferation and migration in papillary thyroid carcinoma cells. (January 2021) - Yan, Ting; Qiu, Wangwang; Song, Jianlu; Fan, Youben; Yang, Zhili
Abstract : The diagnosis and treatment of recurrence and metastasis in papillary thyroid carcinoma (PTC) are still clinical challenges. One of the key factors is the lack of specific diagnostic markers and therapeutic targets for recurrence and metastasis. Single-cell RNA sequencing (scRNA-seq) has emerged as a powerful approach to find specific biomarkers by dissecting expression profiling in human cancers at the resolution of individual cells. Here, we investigated cell profiles of the primary tumor and lymph node metastasis and paracancerous normal tissues in one PTC patient using scRNA-seq, and compared individual cell gene expression differences. The transcriptomes of 11, 805 single cells were profiled, and malignant cells exhibited a profound transcriptional overlap between primary and metastatic lesions, but there were differences in the composition and quantity of non-malignant cells. ARHGAP36 was one of the genes that were highly expressed in almost all of the primary and metastatic malignant cells without non-malignant or normal follicular cells and was then confirmed by immunostaining in a sample cohort. Compared with the paracancerous normal tissue, the expression of ARHGAP36 in primary and metastatic carcinoma tissues was significantly higher as assayed by qRT-PCR. ARHGAP36 knockdown significantly inhibited the proliferation and migration of PTC cells in vitro and involved several proliferation and migration-associated signaling pathways by RNA seq. Our study demonstrated that ARHGAP36 is exclusively expressed in the malignant cells of primary PTC, as well as metastatic lesions, and regulates their proliferation and migration, meaning it can be used as a potential diagnostic marker and therapeutic target molecule.